2018
DOI: 10.1111/anec.12536
|View full text |Cite
|
Sign up to set email alerts
|

Transient left septal fascicular block in the setting of acute coronary syndrome associated with giant slurring variant J‐wave

Abstract: We report a case of acute coronary syndrome with transient prominent anterior QRS forces (PAF) caused by proximal subocclusion of the left anterior descending (LAD) coronary artery before the first septal perforator branch. The ECG change indicates left septal fascicular block (LSFB) with associated slurring-type giant J-wave. Currently, this J-wave variant is considered as a lambda-like wave or QRS-ST-T "triangulation". Its presence is indicative of poor prognosis because of the risk for cardiac arrest as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…In contrast, the existence of conduction defects of the LSF remains controversial. Pérez-Riera et al reported several cases of transient PAF thought to be caused by LSFB in the setting of proximal LAD disease and have stated that the characteristic ECG feature of LSFB is PAF on the horizontal plane (21,22). These ECG findings should be distinguished from other conditions that also produce PAF, such as right ventricular enlargement, lateral myocardial infarction, right bundle branch block, Wolff-Parkinson-White syndrome, hypertrophic cardiomyopathy, and Chagas cardiomyopathy in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the existence of conduction defects of the LSF remains controversial. Pérez-Riera et al reported several cases of transient PAF thought to be caused by LSFB in the setting of proximal LAD disease and have stated that the characteristic ECG feature of LSFB is PAF on the horizontal plane (21,22). These ECG findings should be distinguished from other conditions that also produce PAF, such as right ventricular enlargement, lateral myocardial infarction, right bundle branch block, Wolff-Parkinson-White syndrome, hypertrophic cardiomyopathy, and Chagas cardiomyopathy in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…Vários manuscritos sucessivos do nosso grupo e de outros mostraram que uma grande proporção de casos com LSFB, manifestado por forças anteriores proeminentes do QRS, é causada por obstrução proximal crítica da DAE antes de seu primeiro ramo perfurante septal. [6][7][8][9] Como a DAE é uma continuação do TCE, uma obstrução significativa do TCE pode levar à isquemia na porção média e no território apical do ventrículo esquerdo, onde fica o fascículo septal esquerdo, causando a LSFB.…”
Section: Discussionunclassified
“…Successive publications from our group [6][7][8][9][10][11] and others [12] have provided ECG evidence that blockage of the LSF of the LBB is an incontestable reality. Consequently, the term "hemiblock", unfortunately still the predominant term [13] to denominate the blockages of the LBB fascicles, can be inappropriate according to the new evidence [14], because the LBB is not divided into two but into three fascicles.…”
Section: Discussionmentioning
confidence: 99%